Trends in Britain's eastern trade - Bernd Kunze (Intereconomics, 1972)
Although Britain's trade exchanges with the Comecon-states in 1971 amounted to no more than 3.17 p.c. of its total foreign trade, high growth rates have nevertheless been achieved in recent years.
Keywords: 330; Foreign Trade